Influence of the cobalt content in cobalt iron oxides on the electrocatalytic OER activity. Issue 45 (22nd October 2021) - Saddeler, Sascha; Bendt, Georg; Salamon, Soma; Haase, Felix T.; Landers, Joachim; Timoshenko, Janis; Rettenmaier, Clara; Jeon, Hyo Sang; Bergmann, Arno; Wende, Heiko; Roldan Cuenya, Beatriz; Schulz, Stephan
Abstract : The OER activity of cobalt ferrite nanoparticles depends on the degree of Co redox activity and its change in coordination. Abstract : Sub 10 nm cobalt ferrite Co x Fe3− x O4 ( x ≤ 1.75) nanoparticles and cobalt-rich wüstite (Co x /3 Fe(1− x )/3 )O nanoparticles ( x ≥ 2) were synthesized in a solvothermal approach and characterized by powder X-ray diffraction (PXRD), selected area electron diffraction (SAED), transmission electron microscopy (TEM) as well as energy dispersive X-ray spectroscopy (EDX), IR, Raman, and 57 Fe-Mössbauer spectroscopy. Their electrocatalytic activity in the oxygen evolution reaction (OER) was evaluated and the active state formation was tracked by operando X-ray absorption spectroscopy (XAS). Our studies demonstrate that the cobalt-rich wüstite (Co x /3 Fe(1− x )/3 )O nanoparticles underwent a phase-transformation into the spinels Co x Fe3− x O4 ( x ≥ 2) under the applied OER conditions. The overpotential η 10 at 10 mA cm −2, serving as a benchmark for the OER activity of the cobalt ferrite nanoparticles in alkaline media, was lower than that of magnetite Fe3 O4 even with low cobalt concentrations, reaching a minimum of 350 mV for Co2.25 Fe0.75 O4 with a Tafel slope of 50 mV dec −1 . Finally, we identified that the catalytic activity is linked to the nanoparticle size as well as to the degree of Co redox activity and change in coordination during OER.